Uma abordagem dirigida por modelos para portabilidade entre plataformas de computação em nuvem - Silva, Elias Adriano Nogueira da (Universidade Federal de São Carlos, 2013)
Cloud Computing has potential to revolutionize way that systems are developed and marketed. Among several research gaps related to this new model is the Lock-In. The Lock-In is the difficulty on migrating data and applications from a cloud platform to another. The lack of standardization, as well as other reasons, are causing the problem. This work presents a model-driven(MDE) approach for portability of applications between cloud platforms. With MDE software engineers can work at a high level of abstraction freeing themselves from repetitive tasks related to software implementation and specific details of cloud platforms. Besides portability, MDE brings additional benefits related to traditional software development approaches. The approach presented in this work, basically consists of a DSL and a set of automated transformations for two known cloud platforms Google App Engine and Microsoft Azure. The approach allows the development of cloud applications on a high abstraction level, showing that despite being simple, the elements of the approach are enough to generate many cloud applications, as well as facilitates its development. The evaluation confirms the benefits provided by MDE technologies.
Keywords: Engenharia de software; Computação em nuvem; Desenvolvimento orientado por modelos; Plataforma como serviço (PaaS); Linguagem específica de domínio; Cloud Computing; Model-Driven Engineering; Portability; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO